Community health workers assisting Latinos manage stress and diabetes (CALMS-D): rationale, intervention design, implementation, and process outcomes - Wagner, Julie (Transl Behav Med, 2015)
Latinos have high rates of diabetes and mental distress, but lack appropriate services. A study was designed to compare enhanced standard diabetes care with enhanced standard care plus community health worker (CHW) delivered stress management for Latinos with type 2 diabetes. This paper reports intervention design and process outcomes. A formative process was used to develop and implement an eight-session, group stress management intervention. One hundred twenty-one participants completed baseline assessments; n = 107 attended diabetes education and were then randomized. Recruits reported high credibility and treatment expectancies. Treatment fidelity was high. Participants reported high treatment satisfaction and therapeutic alliance and their diabetes knowledge and affect improved over the short term. Retention and attendance at group sessions was challenging but successful relative to similar trials. This comprehensive and culturally sensitive stress management intervention, delivered by a well-trained CHW, was successfully implemented.